The effectiveness of energy management system on energy efficiency in the building - Abdullah, Haim Hilman; Abubakar, Ahmed; Kaliappen, Narentheren (JBRMR, 2017)
Higher Education sector of any country plays a pivotal role in national development.If such a key sector is weak, there is every likelihood that research, development and innovation will be week.The purpose of this study was to examine the effects of quality culture on university performance.The hypothesis was developed based on the extant literature. Data were collected from Nigerian universities via a structured questionnaire survey using the entire census.Partial Least Squares (PLS) algorithm and bootstrap techniques were used to test the study’s hypothesis.The result revealed that quality culture had a significant positive effect on university performance.Based on the empirical evidence, quality culture is paramount to the success of university; therefore, universities should develop a good practice of quality culture for better performance.Improved university performance can address the problem of low-quality universities.The outcome of this study provides significant contributions to the literature.